1999
DOI: 10.1007/s00585-999-0338-4
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the generation of geomagnetic giant pulsations by drift-bounce resonance ring current instabilities

Abstract: Abstract. Giant pulsations are nearly monochromatic ULF-pulsations of the Earth's magnetic ®eld with periods of about 100 s and amplitudes of up to 40 nT. For one such event ground-magnetic observations as well as simultaneous GEOS-2 magnetic and electric ®eld data and proton¯ux measurements made in the geostationary orbit have been analysed. The observations of the electromagnetic ®eld indicate the excitation of an odd-mode type fundamental ®eld line oscillation. A clear correlation between variations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(129 citation statements)
references
References 30 publications
1
125
0
3
Order By: Relevance
“…[41] Previous studies have reported satellite and groundbased observations of ULF waves associated with the unstable ring current protons [e.g., Hughes et al, 1978;Glassmeier et al, 1999;Wright et al, 2001]. They suggested that the drift-bounce resonance of these protons with nonMaxwellian distribution be responsible for the generation of the observed ULF waves.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] Previous studies have reported satellite and groundbased observations of ULF waves associated with the unstable ring current protons [e.g., Hughes et al, 1978;Glassmeier et al, 1999;Wright et al, 2001]. They suggested that the drift-bounce resonance of these protons with nonMaxwellian distribution be responsible for the generation of the observed ULF waves.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…However, the modulations of ring current ions, especially of O + , with ULF standing waves and the presumed acceleration process of these ions have been rarely reported. In contrast, the ring current ions (particular H + ) were always thought to be a free energy source in generating ULF waves in the magnetosphere [e.g., Hughes et al, 1978;Glassmeier et al, 1999;Wright et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…We still do not fully know what changes can be introduced into this picture by the azimuthal inhomogeneity of the magnetosphere and the associated field-aligned currents, the wide-band character and the possible narrow localization of oscillation sources, the interaction of waves with particles drifting in the magnetosphere, and the active role of the ionosphere. Work in this direction is underway, and this is testified by recently published papers addressing these issues (Salat and Tataronis, 1999;Klimushkin et al, 1995;Mann et al, 1997;Leonovich, 2000;Antonova et al, 2000;Vetoulis and Chen, 1996;Klimushkin, 2000;Glassmeier et al, 1999a;Leonovich and Mazur, 1996). However, the creation of a unified realistic model of MHD waves in the magnetosphere is a long way from now.…”
Section: On the Observation Of Toroidal And Poloidal Alfvén Waves In mentioning
confidence: 99%
“…Ring current ions (mainly H ? ) with a positive gradient in velocity space (Gkioulidou et al 2014) are a potential source of ULF wave generation through drift-bounce resonance (e.g., Hughes et al 1978;Glassmeier et al 1999;. Low-energy ring current O ?…”
Section: Introductionmentioning
confidence: 99%